Diversity-driven knowledge distillation for financial trading using Deep Reinforcement Learning. (August 2021) - Tsantekidis, Avraam; Passalis, Nikolaos; Tefas, Anastasios
Abstract: Deep Reinforcement Learning (RL) is increasingly used for developing financial trading agents for a wide range of tasks. However, optimizing deep RL agents is notoriously difficult and unstable, especially in noisy financial environments, significantly hindering the performance of trading agents. In this work, we present a novel method that improves the training reliability of DRL trading agents building upon the well-known approach of neural network distillation. In the proposed approach, teacher agents are trained in different subsets of RL environment, thus diversifying the policies they learn. Then student agents are trained using distillation from the trained teachers to guide the training process, allowing for better exploring the solution space, while "mimicking" an existing policy/trading strategy provided by the teacher model. The boost in effectiveness of the proposed method comes from the use of diversified ensembles of teachers trained to perform trading for different currencies. This enables us to transfer the common view regarding the most profitable policy to the student, further improving the training stability in noisy financial environments. In the conducted experiments we find that when applying distillation, constraining the teacher models to be diversified can significantly improve their performance of the final student agents. We demonstrate this by providing an extensive evaluation on various financial trading tasks. Furthermore, we also provide additional experiments in the separate domain of control in games using the Procgen environments in order to demonstrate the generality of the proposed method.